Hubungan antara Anemia dan Kejadian Inersia Uteri di RSUD Dr.Moewardi - Dhyani Rahma Sari; Eric Edwin; Kusmadewi Eka Damayanti (Nexus Kedokteran Klinik, 2014)
Background: Anemia is a condition of reduced levels of hemoglobin ( Hb ) which leads to impaired maternal oxygen delivery to form energy in the uterine muscles to make contractions in labor. This research aims to investigate the relation between anemia and prevalence of uterine inertia. Methods: This was an analitic-observational cross sectional study using medical record data from 1 January 2012 30 May 2012 . A sample of 112 subjects was selected from patiens who gave birth with anemia in Moewardi hospital. Sample was conducted in total sampling. Data were analyzed using Chi-Square test. The difference seen from the result by Risk Ratio ( RR ), while the significance of the result seen by the value of p ( p < 0,05 ). Results: Analysis of Chi-Square test showed a statistically significant relationship between anemia and the prevalence of uterine inertia. The result obtained from the analysis was p = 0,001( p < 0,05 ). Conclusions: There is statistically significant relatonship between maternal anemia with prevalence of uterine inertia in Moewardi hospital during period the first of January 2012 the thirtith of May 2012 . Keywords: anemia, labour, uterine inertia.